Comparison Of Anaerobic Lignin Degradation Of Banana Stem Waste Using Mixed Culture From Malaysian Soil And Pure Strains From Soil Culture - N., Zainol; Mohd Faizan, Jamaluddin; R., Abdul-Rahman; N. F., Abdul-Ghaffar; Jailani, Salihon (Global Science Publications, 2014)
Biological lignin degradation is usually achieved by an aerobic process using a fungus. This work reports on the anaerobic lignin degradation process of banana stem waste by comparing the performance of a mixed culture from Malaysian banana plantation soil and the performance of strains isolated from sucha mixed culture. The process for soil mixed culture (SMC) was carried out at ambient temperature in 20-L bioreactor by varying the organic loading rate (OLR) (0.4 g TS/L.d-2 gTS/L.d) and hydraulic retention time (HRT) (3 d-20 d). Conditions for OLR and HRT in this study were based on the best range obtained from literature review. The soil mixed culture for this study was from a banana plantation. It had been acclimatized in anaerobic condition. Factor analysis was applied allowing a screening of the experimental variables (OLR and HRT). In this work the regression coefficients of all models were calculated by using Matlab programming which operates by minimizing the sum of squared differences between the actual and predicted yields. Results from factor analysis have shown that both the variables OLR and HRT have significant effects to anaerobic lignin degradation. Anaerobic lignin degradation was found to be strongly influenced especially by HRT. Increasing HRT could decrease the lignin content of the banana stem waste. The lignin degradation using SMC was between 18% to 54 % based on the 16% initial lignin content. Later pure strains were isolated from the SMC and each strain was screened for the ability to grow efficiently in kraft-lignin medium, as an indicator for its lignin degradation performance in order to find the best strains for lignin degradation. Five potential ligninolytic bacteria (LB) were selected and named as LB 2, LB 8Y, LB 9, LB 8 and LB 35. All selected mesophilic isolates are Gram positive (although they had also exhibited Gram variability reaction), rod-shaped and spore-formers except for the CB 19 isolate which is coccus-shaped and a non-spore former. Furthermore, 16S rRNA gene sequencing results revealed that all the selected isolates come from four different genera of bacteria i.e. Clostridium, Staphylococcus, Paenibacillus and Bacillus. Anaerobic delignification of banana stem waste carried out with each of these strains showed that isolate of LB 2 (Clostridium beijerinckii JCM 8026) and LB 8Y (uncultured, composed of bacterium clone PS3079) were able to delignify the waste with lignin degradation between 12% and 14%. By comparing lignin degradation using SMC and lignin degradation using each isolated pure strain of bacteria from the mixed culture, it was shown that SMC gave the better performance. It can thus be concluded that anaerobic degradation of the complex lignin in banana stem waste can be better performed by soil mixed culture rather than by its individual pure strains. SMC has a very good potential for anaerobic lignin biodegradation since the mixed culture is easier to handle and has higher resistance to environmental changes compared to the isolated pure strains of the SMC bacteria.